Linguistic activism in digital media: the experience of the You Tube channel “Voces Tobas” for education and dissemination (Cuadernos de Extensión Universitaria de la UNLPam, 2026)
This article analyses the “Voces Tobas” project, which focuses on documenting, disseminating and promoting the Toba/Qom language in contemporary contexts where signs of linguistic displacement are evident. In an scenery where the intergenerational transmission of Toba/Qom is declining, this initiative conceives of the production of podcasts and animated videos as a linguistic activism strategy, aimed at creating new species for the circulation of oral tradition, based on a participatory methodology and in collaboration with leaders of a Toba/Qom people. The podcast format, in particular, allows the Toba/Qom language to reach a broad audience, both within and outside the community, and promotes its linguistic and cultural dissemination thanks to the use of open-access digital platforms. Furthermore, the materials designed and disseminated on the YouTube channel ‘Voces Tobas’ constitute fundamental input for their transformation into pedagogical resources for schools and teacher training programs.
Keywords: language activism; toba/qom language; podcast; YouTube; dissemination